Effect of freezing temperature on rate of survival of lactococcus cultures during lyophilization - I. V. Kucherenko; E. V. Kuraeva; E. S. Masegnaya (Пищевые системы, 2024)
The important component in the activities of the collection of starter microorganisms is the preservation of the pool of the strains valuable for industrial production. Lyophilization (also known as freeze drying) is a widely used method for the long-term storage of the collection cultures. The critical parameter of the process of lyophilization is the pre-freezing temperature. This article brings forward the results of researches of the rate of survival of lactococcus strain cultures during their lyophilization with pre-freezing at the temperatures of minus 20 °C, minus 30 °C and minus 55 °C. Reconstituted 10% skim milk was used as the medium for strain culturing and lyophilization. Different reactions were detected among the microorganisms of Lactococcus lactis subsp. lactis, Lactococcus cremoris and Lactococcus lactis subsp. lactis biovar. diacetylactis for their freezing and lyophilization under the tested conditions. The highest rate of survival of lactococcus strains was observed at the freezing temperature of minus 20 °C. The most resistant cultures appeared to be Lactococcus lactis subsp. lactis biovar. diacetylactis — their rate of survival after lyophilization at minus 20 °C amounted to 42.6-57.9%. The lowest survival rate was recorded for Lactococcus cremoris in all freezing modes (from 3.1 to 15.7%). Lyophilization of lactococcus collection cultures ensures high survival rate of the cells.